(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
As readily available medications for obesity and diabetes are reported to cause unwanted side effects, many natural alternatives to control obesity and diabetes are brought forward. Terengganu cherry (Lepisanthes fruticosa (Roxb.) Leenh) is an underutilized fruit in Malaysia that has limited study on its health benefits. Hence, this study aims to investigate the potential anti-obesity and anti-diabetic properties of fermented juice extract of Terengganu cherry (FTCJ). For anti-obesity effects, the impact of FTCJ and PTCJ on adipogenesis was assessed using 3T3-L1 cell differentiation assays. FTCJ inhibited lipid accumulation by 50.45%, 48.40%, and 67.12% at concentrations of 0.25 mg/mL, 0.5 mg/mL, and 0.75 mg/mL, respectively. Although PTCJ exhibited greater lipid accumulation reduction than FTCJ, this effect may be attributed to its cytotoxicity, as observed in cytotoxicity assays. For anti-diabetic effects, α-amylase and α-glucosidase inhibition assays were conducted. Both FTCJ and PTCJ showed no inhibitory activity against α-amylase. However, PTCJ demonstrated significantly higher α-glucosidase inhibition (99.11%) compared to FTCJ (31.72%) at 1.0 mg/mL. These findings suggest that while PTCJ exhibits stronger effects in both adipogenesis inhibition and α-glucosidase inhibition, its potential cytotoxicity raises concerns. In contrast, FTCJ exhibits promising anti-obesity effects with lower cytotoxicity, highlighting its potential as a natural alternative for managing obesity and diabetes. Further studies are recommended to explore its mechanisms and potential applications.